Intraductal Proliferative Lesions of the Breast—Terminology and Biology Matter: Premalignant Lesions or Preinvasive Cancer?. (10th May 2012) - Costarelli, Leopoldo; Campagna, Domenico; Mauri, Maria; Fortunato, Lucio
Abstract : Morphological criteria for the diagnosis of intraductal proliferative lesions of the breast have been an object of research and much controversy, and its terminology is rather confusing. Knowledge of the molecular aspects of this disease probably necessitates further research to clarify if these entities can be identified as breast cancer precursors or as a malignant preinvasive disease. These issues are of great interest not only for their biological implications, but also to the clinician who must understand the disease and direct therapies. Molecular studies have shown that epitheliosis (usual ductal hyperplasia) is not monoclonal, while malignant lesions (atypical ductal hyperplasia, flat epithelial atypia, low-grade and high-grade intraductal carcinoma) constantly show these characteristics. These malignant lesions, classified with a DIN grading system (ductal intraepithelial neoplasia), are not obligate precursors of invasive ductal carcinoma and do not represent different evolving grades in a linear model of cancerogenesis. Breast cancerogenesis probably has different pathways with different morphologic precursors.